Escaping to the East? Relocation of business activities to and from Hungary, 2003-2011 - Magdolna Sass; Gábor Hunya (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
While the increased frequency of relocation of productive capacities to lower wage countries from developed economies has given rise to discussions concerning job losses and de-industrialisation, developments in the host countries of relocation have been widely neglected. Hungary, together with other new EU member countries, is one of the net beneficiary countries of relocation especially from the developed EU-15 countries. Macro-data can be used only to a limited extent to describe the complex phenomenon of relocation; case study evidence and company level analysis can shed light on details and short-term changes. We compiled a comprehensive relocation database in Hungary for the nine-year period between 2003 and 2011. In this paper we analyse this database and compare the results with those of the literature. We shed light on details concerning the nationality of relocating companies, the sectors and foreign locations affected and the job creation/loss impact. Finally we discuss the effects of the recent crisis when the number of greenfield investment projects declined, but the number of relocations to Hungary increased.
Keywords: F21; F23; 330; relocation; Hungary; multinational corporations; offshoring; offshore outsourcing; crisis